Spectrum of CT scan findings in non-traumatic acute abdominal pain: An observational study. - Sidar, Chhani Lal Narsingh; Laxmi, Vidya (Student's Journal of Health Research Africa, 2025)
Background Non-traumatic acute abdominal pain is a frequent emergency presentation with diverse etiologies. Clinical evaluation alone is often inconclusive, necessitating imaging. Computed tomography (CT) is increasingly recognized as a rapid and reliable modality for accurate diagnosis and management planning. Objectives To evaluate the spectrum of CT scan findings in patients presenting with non-traumatic acute abdominal pain and determine its diagnostic yield. Methods This hospital-based observational study enrolled 100 consecutive patients aged 18–78 years who presented with acute abdominal pain of non-traumatic origin. All patients underwent CT imaging. Demographic characteristics, symptom profiles, and CT findings were documented and analyzed. The diagnostic yield of CT in establishing definitive etiologies was assessed. Results The mean age of participants was 42.6 ± 15.8 years, with males comprising 58% and females 42%. Generalized abdominal pain was the most common presentation (62%), followed by right iliac fossa pain (24%). CT identified acute appendicitis in 28%, urolithiasis with obstructive uropathy in 20%, diverticulitis in 12%, pancreatitis in 10%, and hepatobiliary pathology in 8%. Less frequent findings included intestinal obstruction (7%), inflammatory colitis (5%), perforated viscus (4%), adnexal pathology (3%), mesenteric ischemia (2%), and miscellaneous causes (1%). No significant abnormality was observed in 10% of patients. Overall, CT provided a definitive diagnosis in 90% of cases. Conclusion CT scan proved highly effective in evaluating non-traumatic acute abdominal pain, offering rapid, accurate diagnoses across a wide etiological spectrum. Its routine use in emergency settings enhances decision-making and improves patient outcomes. Recommendations CT should be integrated into standard diagnostic protocols for acute abdominal pain in emergency care. Future studies should explore radiation dose reduction techniques, cost-effectiveness, and comparative accuracy with ultrasonography and MRI.